Strategi Advokasi Anti Diskriminasi sebagai Solusi Perlindungan terhadap Kelompok Rentan Albino - Nurul Mawadda; Andi Putri Dewanti; Andi Ahmad Alfarabi; Nurul Aisyah; Nurfitah Ersya Mubarak; Andi Syahwiah Andi Sapiddin (LPPM Universitas Ekasakti Padang, 2023)
In addressing the issue of discrimination against albino individuals, a specific and comprehensive approach and strategy are needed to prioritize human rights protection principles such as equality, equity, mutual respect, and inclusivity among individuals. This approach is known as